4n+7-2n=3n-3

Simple and best practice solution for 4n+7-2n=3n-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n+7-2n=3n-3 equation:


Simplifying
4n + 7 + -2n = 3n + -3

Reorder the terms:
7 + 4n + -2n = 3n + -3

Combine like terms: 4n + -2n = 2n
7 + 2n = 3n + -3

Reorder the terms:
7 + 2n = -3 + 3n

Solving
7 + 2n = -3 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
7 + 2n + -3n = -3 + 3n + -3n

Combine like terms: 2n + -3n = -1n
7 + -1n = -3 + 3n + -3n

Combine like terms: 3n + -3n = 0
7 + -1n = -3 + 0
7 + -1n = -3

Add '-7' to each side of the equation.
7 + -7 + -1n = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -1n = -3 + -7
-1n = -3 + -7

Combine like terms: -3 + -7 = -10
-1n = -10

Divide each side by '-1'.
n = 10

Simplifying
n = 10

See similar equations:

| 60x=50(x+1) | | 2x^2-16x=7 | | 24y= | | x^2-7xy+6y^2=equation | | 2x^2+12x=12 | | 12x-5=3x+45 | | 180-x=279 | | 180-x=179 | | 160-x=88 | | ln(x)=0.0023 | | 8p^3-343/9 | | 6xwhat=96 | | 4x^2-1x-6=0 | | (1+x^4)dy+x(4y^2+1)dx=0 | | 646.8+-1.2y= | | 5.76X^2+2.86X-1.35=8 | | 10+y=10+0.5y | | 7m^2-4m=3m*(m-7/2) | | 3m*(m-7/2) | | 6x-sqrtx=12 | | 4/5x-10=54 | | f(x)=[x-3] | | 91+19m=376 | | 15x+45x-4y= | | 34n-104=338 | | 6m+6.75=63.75 | | 5x^2-6x=4x^2+6x-13 | | 2a+2x+x=70 | | 3x-69=27 | | 4y+7z=17 | | x=385 | | 4n-7=37 |

Equations solver categories